THE SYSTEM OF EXERCISES FOR PUPILS WITH SPECIAL EDUCATIONAL NEEDS AT THE LESSONS OF ENGLISH - Melekhova, V.S.; Skrypnik, Yu.N. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
For increasing the effectiveness of teaching students with special educational needs the authors of the article developed the system of exercises on mental processes development such as memory, cognition, attention, speech and physical abilities, mainly motor skills taking into account the psychological prerequisites, including the need to carry out work aimed at increasing the level of intellectual abilities, perseverance and motivation of schoolchildren in learning a foreign language.
Keywords: inclusive education; pedagogical support; adaptation; motivation; mental and physical health; exercises; learning effectiveness